To Determine the Validity and Reliability of Performance Failure Appraisal Inventory - Behrouz Abdoli; Nasour Ahmadi; Elham Azimzadeh; Javad Afshari (University of Tehran, 2013)
Success is satisfactory for any athlete. However, some athletes will face anxietyin novel circumstances and fear of future will prevent them from improving. Fearof failure is accompanied with stress and adaptation to stress is the most importantissue for an effective decision. The aim of this study was to examine validity andreliability of performance failure appraisal inventory (PFAI). For this purpose,203 athlete university students (93 women and 110 men who aged between 19 and23 with the physical activity record 7.70±4.4) completed PFAI. Confirmatoryfactor analysis was used to examine construct validity, Cronbach's alphacoefficient to examine internal consistency of the items of each factor, and Pearsoncorrelation coefficient to examine inter-factor reliability. Results of confirmatoryfactor analysis confirmed five factors in PFAI: fear of devaluing one's self-esteem(4 items), fear of an uncertain future (4 items), fear of upsetting importantindividuals (5 items), fear of experiencing shame and embarrassment (7 items) andfear of losing important individuals' interest (5 items). Correlation analysisshowed an acceptable correlation between all of these factors and fear of failure.The results of Cronbach's alpha coefficient showed acceptable internal consistencyof items of each subscale.